Reasons for high school students dropping out of physical education classes - Maffei, Willer Soares [UNESP]; Moraes, Mayra Grava [UNESP]; Cassan Bonome Vanzelli, Silvia Regina [UNESP]; Kato, Debora Navarro [UNESP]; Roque Silva, Talita Fabiana [UNESP]; Rcis, Gleyce Soarcs [UNESP]; Lopes Vcrardi, Carlos Eduardo [UNESP] (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2021)
This research sought to analyze the dynamics of physical education classes in the 3rd year of high school and to recognize the profile of the classes and the involvement of students, understanding the reasons that lead them to drop out. This is a descriptive and cross-sectional study. A questionnaire was used to gather data on the participation of 517 high school students in physical education classes in the 3rd year of high school in state public schools in the interior of Sim Paulo. For the analysis of the information, a descriptive analysis and content analysis were used. The initial results showed that 44 % of the sample had some bather that prevents them from taking classes. Of this percentage, 74.6 % were girls, who were the majority, and who answered open questions about non-participation. It is concluded that approximately half of the participating students, mainly girls, participate little, or do not participate in physical education classes, this result being related to the methodology and the selection of content developed by the teacher. The role of physical education classes is to serve all students, respecting their differences, stimulating their potential to contribute so that they are proactive, critical, and autonomous in relation to their health and quality of life.
Keywords: motivation; high school; school physical education; learning; dropout